Plastin 3 in X-Linked Osteoporosis: Imbalance of Ca2+-Dependent Regulation Is Equivalent to Protein Loss - Schwebach, Christopher L.; Kudryashova, Elena; Kudryashov, Dmitri S. (Frontiers in Cell and Developmental Biology, 2021)
Osteogenesis imperfecta is a genetic disorder disrupting bone development and remodeling. The primary causes of osteogenesis imperfecta are pathogenic variants of collagen and collagen processing genes. However, recently variants of the actin bundling protein plastin 3 have been identified as another source of osteogenesis imperfecta. Plastin 3 is a highly conserved protein involved in several important cellular structures and processes and is controlled by intracellular Ca2+ which potently inhibits its actin bundling activity. The precise mechanisms by which plastin 3 causes osteogenesis imperfecta remain unclear, but recent advances have contributed to our understanding of bone development and the actin cytoskeleton. Here, we review the link between plastin 3 and osteogenesis imperfecta highlighting in vitro studies and emphasizing the importance of Ca2+ regulation in the localization and functionality of plastin 3.